Clinical Manifestations and Laboratory Examination Findings of Hepatocellular Carcinoma at a Tertiary Care Facility in Bandung: An Annual Observation Study - Grace Amanda Maharani; Eka Surya Nugraha; Adhi Kristianto Sugianli (Althea Medical Journal, 2021)
Background: Hepatocellular Carcinoma (HCC) is the most prevalent liver cancer with high mortality. Early detection is important for better patient outcomes. The aim of this study was to explore clinical manifestations and laboratory examinations among HCC patients in a tertiary care facility.Methods: This was a cross-sectional descriptive study with a total sampling method, reviewing the medical record of patients with HCC in the Outpatient Clinic of Dr. Hasan Sadikin General Hospital between January to December 2019. Clinical manifestations, laboratory findings, and imaging results data were collected.Results: Of the 112 HCC patients included in this study, the HCC findings among new patients at the outpatient clinic were 8.4%, with hepatitis B (80.8%) as the major etiology. Complaints of abdominal pain (65.2%) was frequent. Aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels were increased in 89.8% and 67% of patients, as well as total bilirubin levels in 58.8% of patients. In contrast, hemoglobin and albumin levels decreased in 55.3% and 78.1% of patients, respectively. The characteristics of tumor were mainly multinodular, with a size of 3-10 cm.Conclusions: The annual proportion of HCC in Dr. Hasan Sadikin General Hospital in 2019 is 8.4% among all outpatient gastrointestinal and hepatology cases, with hepatitis B as the most common etiology. Abdominal pain is the predominantly prevalent clinical manifestation with increased ALT and AST levels.